Design of Split AC-Based Central Equipment as a Learning Media Tool in Refrigeration and Air Conditioning Engineering Courses - M. Indra Martadinata; Parjan Parjan; Annisa Baby Callista; Wahyudi Saputra (International Journal of Educational Review, 2024)
Education is a humanistic process, and its implementation increases students’ competence in higher education. The emphasis on increasing competence is explained through the performance of the Kurikulum Merdeka (Independent Curriculum). This research highlights the need for effective learning media, especially in Refrigeration and Air Conditioning Engineering courses, which include an understanding of Air Conditioning Systems (ACS). This course curriculum aims to provide a sense of Air Conditioning (AC), including Central AC. However, a lack of learning media in the laboratory requires cadets to visit the nearest airport for practicum. This research aims to design an innovation in creating central equipment learning media designs based on Split AC. This quantitative research method was conducted, with data collection through observation, literature study, questionnaires, and Likert scale analysis. The author determined the population of the Airport Engineering Technology Study Program cadets at the 3rd Batch of the Politeknik Penerbangan Palembang, totaling 22 cadets. This research uses purposive judgment sampling or sampling with purpose or consideration because cadets are considered to understand the problem to be studied. The questionnaire results showed a high need for learning media development, with a mark of 82.3%. Therefore, developing this learning medium is needed to increase cadets’ understanding and competence in refrigeration and air conditioning engineering courses.